Upaya Meningkatkan Pemahaman Bermain Bolavoli melalui Model Role Playing - Noerfalah, Dini; Lubay, Lukmannul Haqim; Budiman, Didin (Universitas Pendidikan Indonesia, 2019)
The purpose of this research is to investigate how role playing method can improve student understanding in volleyball games activities. This research use class action research. The research used in two cycle, every cycle have research action that done twice. The subject of this research is 30 students of level 5 class from one elementary school in Bandung. (12 boys, 18 girls). Role playing models combine with GPAI instrument. Data is analyzed using percentage technic and associated with games performance. This research showed that role playing models can improve student understanding in volleyball games. AbstrakPenelitian ini bertujuan untuk mengetahui apakah penerapan model role playing dapat meningkatkan pemahaman bermain siswa dalam bermain bolavoli. Penelitian ini menggunakan penelitian tindakan kelas. Penelitian dilakukan dalam dua siklus, setiap siklus dilaksanakan sebanyak dua kali tindakan penelitian. Subjek penelitian adalah kelas V disalah satu sekolah dasar di Kota Bandung sebanyak 30 siswa (laki-laki: 12; perempuan: 18). Model role playing dikombinasikan dengan instrument Game Performance Analisis Instrumen. Data dianalisis menggunakan teknik persentase dan dikaitkan dengan keterampilan bermain. Hasil penelitian menunjukan model pembelajaran role playing dapat meningkatkan pemahaman bermain bolavoli.